O desafio biográfico ou como se escrever uma vida: a (des)construção da figura heroica de Santos-Dumont a partir de O brasileiro voador - Dungue, Cléber Luís (2011)
The present research tries to question if a story that has been told so many times Santos-Dumont, a national hero, the airplane inventor and father of aviation can still bring something new, singular, able to break the expectancy of the reader. The life and history of Santos-Dumont have already been the theme of hundreds of biographies, many of them written using a traditional model that tries to develop, enhance and perpetuate the heroic image of the aviator. This happens, mainly, because of the proximity of the aviator to the classical myths and of the use of particular laudatory words. The image of the hero is made up from this vision that is one-dimensional and infallible. Walk together, therefore, with the very shape of the speech that the states it, based on a monological truth, absolute, which is intended indisputable. Among so many biographies that try to rebuild the life of Santos-Dumont, and fail precisely at this point, there is one that stands out as a parodic-novel O Brasileiro Voador by Márcio Souza. Facing the impossibility to distinguish the factual from the invention, among the shifts terrains of biographies, this Amazonian author sorts out the elements from original documents about Santos-Dumont in a fictional context. Without giving away the data research, the text is built from the unfolding, moving and condensing the facts that really happened, and they are explored according to the existing, possibilities in the literary environment. When re-organizing the conventional biographies data using parody and fiction, the act of creation of Márcio Souza, alters, erasures and transforms the official history of Santos-Dumont. Thereby, both the myth and the structure of the traditional biographical speech itself are deconstructed by the Amazonian author, showing up the fictional line that holds every biography. Through this process, the parody is precisely the most efficient strategy to break up the sedimented tradition and extract from it, not the hero, but the man with his conflicts and contradictions